Prevalence and predictors of airflow obstruction in an HIV tertiary care clinic in Montreal, Canada: a cross‐sectional study. Issue 3 (8th January 2019) - Costiniuk, CT; Nitulescu, R; Saneei, Z; Wasef, N; Salahuddin, S; Wasef, D; Young, J; de Castro, C; Routy, JP; Lebouché, B; Cox, J; Smith, BM; et al.
Abstract : Objectives: The reported prevalence of chronic obstructive pulmonary disease (COPD) in people living with HIV (PLWHIV) varies widely. Our objective was to estimate the prevalence of airflow obstruction and COPD in unselected PLWHIV and identify characteristics that increase the risk of nonreversible airflow obstruction in order to guide case finding strategies for COPD. Methods: All adults attending the Chronic Viral Illness Service were invited to participate in the study, regardless of smoking status or history of known COPD/asthma. Individuals underwent spirometric testing both before and after use of a salbutamol bronchodilator. Airflow obstruction was defined as forced expiratory volume in 1 s (FEV1 )/forced vital capacity (FVC) < 0.7 post‐bronchodilation, whereas COPD was defined as FEV1 /FVC < 0.7 post‐bronchodilation and Medical Research Council (MRC) score > 2. Multivariate logistic regression was used to evaluate risk factors associated with airflow obstruction, reported as adjusted odds ratios (aORs). Results: Five hundred and three participants successfully completed spirometry testing. The median (Q1; Q3) age was 52 (44; 58) years. The median (Q1; Q3) CD4 count was 598 (438; 784) cells/μL and the median (Q1; Q3) nadir CD4 count was 224 (121; 351) cells/μL. There were 119 (24%) current smokers and 145 (29%) former smokers. Among those screened, 54 (11%) had airflow obstruction whereas three (1%) of the participants had COPD. Factors that were associated with airflow obstruction included a history of smoking [aOR 2.2; 95% confidence interval (CI) 1.1; 4.7], older age (aOR 1.6; 95% CI 1.2; 2.2), and lower CD4 count (aOR 0.8; 95% CI 0.7; 1.0). Conclusions: Airflow obstruction was relatively uncommon. Our findings suggest that PLWHIV who are ≥50 years old, smokers and those with nadir CD4 counts ≤ 200 cells/μL could be targeted to undergo spirometry to diagnose chronic airflow obstruction.